IMPLEMENTASI METODE CONTEXTUAL TEACHING AND LEARNING BERBASIS KEARIFAN LOKAL BERBANTUAN MEDIA PODCAST UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS NEGOSIASI PADA SISWA - Teguh Alfaidzin; Ida Ayu Made Wedasuwari (Jurnal Santiaji Pendidikan (JSP), 2026)
This study aims to determine the implementation of the contextual teaching and learning (CTL) method based on local wisdom assisted by podcast media to improve negotiation text writing skills in Indonesian language learning for grade X students at SMAN 5 Denpasar. The novelty of this study lies in the integration of Balinese local wisdom values ​​into the contextual learning process which is packaged innovatively through podcast media, so as to present an authentic, relevant, and interesting learning experience for digital generation students. This study is a classroom action research. Quantitative and qualitative data were collected through the implementation of observation and test actions. The average score of 35 students in the pre-test was 50.12 with a percentage of 0% of students achieving the Learning Objectives Achievement Criteria (KKTP), then there was an increase in the average in cycle I which was 72.86 with a percentage of 57.14% or 20 students who achieved KKTP and the completeness of the action in cycle II with an average score of 84.17 with a percentage of 91.43% or 32 students who achieved KKTP so that the implementation of the cycle was not continued. The results of the study indicate that the implementation of local wisdom-based CTL with the aid of podcast media significantly improved students' negotiation text writing skills, both in terms of structure, linguistic rules, and understanding of cultural context. These findings recommend the development of a learning model based on Balinese local wisdom and the use of innovative digital media to strengthen 21st-century literacy competencies in schools